1999
DOI: 10.1007/pl00009075
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an Aspergillus niger glucose oxidase production process

Abstract: The purpose of the present study was to ascertain the optimal concentration of dissolved oxygen in order to maximize the intracellular glucose oxidase formation in Aspergillus niger. Cultivations performed in a 3.5 l laboratory reactor showed that a dissolved oxygen concentration at 3% of saturation at a total pressure of 1.2 bar was optimal for maximizing intracellular glucose oxidase activity. Cultivations performed at higher dissolved oxygen concentrations did not produce as much glucose oxidase as those pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Early studies on A. niger GOX production and purification treated the enzyme as intracellular [13][14][15], a fact supported by the claim of its localization in peroxisomes [16]. While there also appeared reports dealing with the optimization of GOX production from A. niger measuring only the extracellular levels of the enzyme [17,18], the prevalent viewpoint on the matter is that the enzyme is mostly cell associated and it appears in the extracellular medium as a result of an active secretion process, a situation described for both wild-type [19][20][21][22] and recombinant A. niger strains [23,24]. The above fact is also supported by immunocytochemical studies that revealed that the bulk of the enzyme is localized in the cell wall [25].…”
Section: Introductionmentioning
confidence: 93%
“…Early studies on A. niger GOX production and purification treated the enzyme as intracellular [13][14][15], a fact supported by the claim of its localization in peroxisomes [16]. While there also appeared reports dealing with the optimization of GOX production from A. niger measuring only the extracellular levels of the enzyme [17,18], the prevalent viewpoint on the matter is that the enzyme is mostly cell associated and it appears in the extracellular medium as a result of an active secretion process, a situation described for both wild-type [19][20][21][22] and recombinant A. niger strains [23,24]. The above fact is also supported by immunocytochemical studies that revealed that the bulk of the enzyme is localized in the cell wall [25].…”
Section: Introductionmentioning
confidence: 93%
“…The effects of different mutants of A. niger strains on GO production were reported in the literature. [31,32] This indicates that different strains of the same microorganism may exhibit fundamental metabolic differences even if the same metabolite is produced.…”
Section: Selection Of a Niger Isolates For Go Production On Rhpmmentioning
confidence: 98%